Pass the Source—Journalism’s Confidentiality Bane in the Face of Legislative Onslaughts - Fernandez, Joseph (Sage Publications, 2017)
‘Journalism under siege’ proclaimed the cover of The Walkley Magazine, an Australian publication dedicated to promoting journalism excellence in its March 2017 issue. This headline reflects the severe disruption journalism is experiencing globally. Facts used to be facts and news was news but now we have ‘alternative facts’ and ‘fake news’ (Media Watch, 2017). Against this backdrop, a persistent dilemma for journalism has been the impact of the law on journalists relying on confidential sources who play a critical part in providing access to information. The journalism profession’s apparent source protection gains have been undermined by legislative and other assaults, and it has had a chilling effect on journalists’ contacts with confidential sources. The Australian journalists’ union, the Media Alliance, has warned that ‘it is only a matter of time’ before a journalist is convicted for refusing to disclose a confidential source (Murphy, 2017, p. 3). This article builds on earlier work examining how Australian journalists are coping in their dealings with confidential sources. This article (a) reports on the findings from an Australian study into journalists’ confidential sources and (b) identifies lessons and reform potentials arising from these findings.